2017
DOI: 10.1177/1753425917695446
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity caspase-4 binding to LPS presented as high molecular mass aggregates or in outer membrane vesicles

Abstract: Caspases of the non-canonical inflammasome (caspases-4/5/11) directly bind endotoxin (LOS/LPS) and can be activated in the absence of any co-factors. Models of LPS-induced caspase activation have postulated that 1:1 binding of endotoxin monomers to caspase trigger caspase oligomerization and activation, analogous to that established for endotoxin-induced activation of MD-2/TLR4. However, using metabolically radiolabeled LOS and LPS, we now show high affinity and selective binding of caspase-4 to high molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…As judged by gel electrophoresis and size‐exclusion chromatography, binding of caspase‐4/5/11 to purified LPS yields high molecular weight caspase/LPS complexes, consistent with binding of caspase to the naturally aggregated form of LPS . Using catalytically inactive purified recombinant pro‐caspase‐4 to model the initial interactions with LPS, we have shown that recombinant pro‐caspase‐4 interacts with high affinity both to purified LPS aggregates and to OMVs but not to protoplasts of Gram‐positive bacteria or complexes of LPS monomers with CD14 . Taken together, these findings seem most compatible with preferential interactions of pro‐caspase‐4/5/11 with the multiple anionic groups (e.g., phosphates, acidic sugars) of LPS clustered in close proximity at an LPS‐rich interface …”
Section: What Is the Form Of Lps That Engages Cytosolic Pro‐caspase‐4supporting
confidence: 62%
“…As judged by gel electrophoresis and size‐exclusion chromatography, binding of caspase‐4/5/11 to purified LPS yields high molecular weight caspase/LPS complexes, consistent with binding of caspase to the naturally aggregated form of LPS . Using catalytically inactive purified recombinant pro‐caspase‐4 to model the initial interactions with LPS, we have shown that recombinant pro‐caspase‐4 interacts with high affinity both to purified LPS aggregates and to OMVs but not to protoplasts of Gram‐positive bacteria or complexes of LPS monomers with CD14 . Taken together, these findings seem most compatible with preferential interactions of pro‐caspase‐4/5/11 with the multiple anionic groups (e.g., phosphates, acidic sugars) of LPS clustered in close proximity at an LPS‐rich interface …”
Section: What Is the Form Of Lps That Engages Cytosolic Pro‐caspase‐4supporting
confidence: 62%
“…The sensing of OMVs by the noncanonical inflammasome sensors in human cells, namely caspase‐4 and ‐5, have not been thoroughly examined previously. A recent study showed that aggregates of LPS, as well as OMVs from Neisseria meningitidis , bound to caspase‐4 . We have previously shown that caspase‐4 is required for sensing of free LPS from S. Typhimurium; however, both caspase‐4 and ‐5 are involved in the sensing of LPS present in live bacteria .…”
Section: Discussionmentioning
confidence: 97%
“…Our finding that LPS promotes the close association of GBPs with pathogen membranes could indeed also be explained by a model in which GBPs form part of an LPS‐sensing macromolecular complex that assembles on the bacterial outer membrane and that contains LPS, GBPs, and caspase‐11. Indeed, it has been suggested that OMVs present LPS to human caspase‐4 (Wacker et al , ), and caspase‐11 has been found to localize to OMVs or even cytosolic bacteria (Thurston et al , ; Vanaja et al , ), although these preliminary observations will need independent confirmation and additional controls. As part of such a complex, GBPs could, for example, disrupt the outer bacterial membrane and help LPS, namely its lipid A moiety, to get more accessible for recognition by caspase‐11.…”
Section: Discussionmentioning
confidence: 99%